2016
DOI: 10.14737/journal.aavs/2016/4.7.376.380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Orange and Banana Peels on the Growth Performance of Broilers

Abstract: | This research was conducted for evaluation of various levels of orange and banana peels on growth performance of broilers and also predicted cost effective feed. A total of 250 day-old healthy Hubbard broiler chicks were randomly selected and divided into five groups (50 chicks / group). The group A served as control on basal diet. The groups B1 and B2 treated with orange peel (1.5 and 3.0 %), and C1/C2 treated with banana peel (1.5 and 3.0 %) in mutually starter and grower ration throughout whole feeding tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 7 publications
0
12
0
1
Order By: Relevance
“…Similarly, some studies have been reported comparable growth performance of aquatic animals including abalone fed the diets substituting MA with food and plant by‐products (tuna by‐product, tunic meal of sea squirt, rice bran and white radish by‐product) for fish meal and MA (Choi et al, ; Jeon, Kim, Myung, & Cho, ; Lee et al, ; Lee, Kim, Choi, et al, ; Lee et al, ). The desirable effect of citrus peel on growth of land animals, such as rats (Lim, Lee, & Kim, ), broiler (Ebrahimi, Qotbi, Seidavi, & Bagar, ; Siyal et al, ) and rabbit (Ojabo, Adenkola, & Odaudu, ), has also been reported. However, this study reported the desirable substitution effect of CPB for MA ( U. pinnatifida ) in feed on growth performance and high stress resistant of abalone to air exposure stressor for the first time.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, some studies have been reported comparable growth performance of aquatic animals including abalone fed the diets substituting MA with food and plant by‐products (tuna by‐product, tunic meal of sea squirt, rice bran and white radish by‐product) for fish meal and MA (Choi et al, ; Jeon, Kim, Myung, & Cho, ; Lee et al, ; Lee, Kim, Choi, et al, ; Lee et al, ). The desirable effect of citrus peel on growth of land animals, such as rats (Lim, Lee, & Kim, ), broiler (Ebrahimi, Qotbi, Seidavi, & Bagar, ; Siyal et al, ) and rabbit (Ojabo, Adenkola, & Odaudu, ), has also been reported. However, this study reported the desirable substitution effect of CPB for MA ( U. pinnatifida ) in feed on growth performance and high stress resistant of abalone to air exposure stressor for the first time.…”
Section: Discussionmentioning
confidence: 95%
“…A study was conducted for the evaluation of various levels of orange and banana peels on growth performance of broiler chicks. Both peels increased the growth performance of broilers (Siyal et al, 2016). In similar, El-Boushy & Van der Poel (2013) revealed that orange fruits by-products enhanced the FCR of animals in poultry sector when compared with traditional feed.…”
Section: Discussionmentioning
confidence: 88%
“…Bio converting agricultural wastes into usable biomass is sustainable ways to produce food sources for domestic animal consumption. Abel et al [25] and Siyal et al [26] claimed banana peels could be recycled and reused for broiler chickens diet. Our result showed that TML reached to 0.09% increment in terms of FCR when banana peel was used as sole feeding material.…”
Section: Discussionmentioning
confidence: 99%